Upaya Meningkatkan Kemampuan Berhitung Melalui Kotak Pintar Pada Kelompok B Semester I Tk Ngudi Utomo Gondang Kecamatan Ngawen Kabupaten Blora Tahun 2015/2016 - SULISTIYOWATI, SULISTIYOWATI; , Drs. M. Yahya, M.Si (2015)
Muhammadiyah Surakarta. August, 2015 This research purpose is research to improve the numeracy skills of children through smart box. This research is a classroom action research conducted in two cycles and each cycle outsmart conducted two meetings. The subjects of this study is children kindergarten Ngudi Group B Utomo Gondang District of Ngawen Blora totaling 13 children as recipients of actions, researcher and teacher colleagues as giving action. The data collected in this study is data about the numeracy skills of children and data on teacher learning through smart box. Both of these data were collected through observation. Data were analyzed with the child's ability to count and a comparative analysis of data on teacher learning through smart grid is analyzed by interactive analysis. The results of the analysis showed that the average prasiklus numeracy skills the child reaches 56% means that the child's ability to count only beginning to develop. After the first cycle measures the average child's ability to count reached 68%, which means that the numeracy skills that children develop according to expectations. After the second cycle measures the average child's ability to count increased by 87% means that children develop numeracy skills very baik. Main of this study is that through a smart grid can improve numeracy skills of children in kindergarten Ngudi Group B Utomo Gondang District of Ngawen Blora.